2021
DOI: 10.1074/jbc.ra120.015420
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation of the ubiquitin ligase IDOL decreases LDL receptor levels and is reversed by SENP1

Abstract: Inducible degrader of the low-density lipoprotein receptor (IDOL) is an E3 ubiquitin ligase mediating degradation of low-density lipoprotein (LDL) receptor (LDLR). IDOL also controls its own stability through autoubiquitination, primarily at lysine 293. Whether IDOL may undergo other forms of post-translational modification is unknown. In this study, we show that IDOL can be modified by small ubiquitin-like modifier 1 (SUMO1) at the K293 residue at least. The SUMOylation of IDOL counteracts its ubiquitination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…We further knocked down KLKB1 using siRNA (Figure S1F) and detected increased levels of LDLR protein (Figure 1E). Inducible degrader of the LDLR as the E3 ubiquitin ligase known to mediate LDLR degradation [26][27][28] was the positive control. In line with LDLR elevation, the uptake of DiI-labeled LDL was dramatically increased in KLKB1 knockdown cells (Figure 1F and 1G).…”
Section: Results Pk Promotes Ldlr Degradationmentioning
confidence: 99%
“…We further knocked down KLKB1 using siRNA (Figure S1F) and detected increased levels of LDLR protein (Figure 1E). Inducible degrader of the LDLR as the E3 ubiquitin ligase known to mediate LDLR degradation [26][27][28] was the positive control. In line with LDLR elevation, the uptake of DiI-labeled LDL was dramatically increased in KLKB1 knockdown cells (Figure 1F and 1G).…”
Section: Results Pk Promotes Ldlr Degradationmentioning
confidence: 99%
“…Upregulation of SREBP2 has been known to activate PCSK9 expression in the HepG2 hepatocytes. Hence, it can be inferred that inhibition of SREBP2 enables the downregulation of PCSK9 expression, increasing LDL uptake. Moreover, the current study demonstrated that 8′ Z ,11′ Z -octadecadienyl-6,8-dihydroxyisocoumarin ( 1 ) and 5- O -methylembelin ( 3 ) slightly downregulate IDOL mRNA expression. In contrast, LXRs induce the transcriptional expression of IDOL, which is involved in degrading LDLR and thereby inhibiting LDL uptake. …”
Section: Resultsmentioning
confidence: 99%
“…The known structure compounds (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) were identified by comparison of their spectroscopic data with the reported values, as 5-O-methylembelin (3), 20 5-O-methylrapanone (4), 21 9-hydroxy-(9S,10E,12Z,15Z)-octadecatrienoic acid (5), 22 9-oxo-(10E,12E)-octadecadienoic acid (6), 23 9-oxo-(10E,12Z)-octadecadienoic acid (7), 23 2,3-dihydroxypropyl-(10Z,13Z)-nonadecadienoate (8), 24 2,3-dihydroxypropylpentadecadienoate ( 9), 25 1-monopalmitoyl-rac-glycerol (10), 26 monononadecanoin (11), 27 methyl linoleate ( 12), 6 linoleic acid (13), 6 oleic acid ( 14), 24 capric acid (15), 28 lauric acid (16), 29 palmitic acid (17), 30 stearic acid (18), 31 (+)-demethoxylpinoresinol (19), 6 (+)-pinoresinol (20), 6 trans-cinnamic acid (21), 32 and cis-ferulic acid (22). 33 The known compounds (3)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tertiary structures and modification processes of SUMOylation are highly similar to those of ubiquitination (39). For example, the K293 residue in low-density lipoprotein receptor (IDOL) is modified by both SUMOylation and ubiquitination, wherein SUMOylation can counteract ubiquitination to increase the levels of IDOL (40). The deubiquitinating enzyme ubiquitin carboxy-terminal hydrolase 37 (USP37) is modified by SUMOylation and ubiquitination at different sites, and SUMOylation at K452 promotes subsequent ubiquitination of K148 and K389 (41).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%